Co-hydrothermal carbonization of rape straw and microalgae: pH-enhanced carbonization process to obtain clean hydrochar. (15th October 2022) - Liu, Xiangmin; Fan, Yuwei; Zhai, Yunbo; Liu, Xiaoping; Wang, Zhexian; Zhu, Ya; Shi, Haoran; Li, Caiting; Zhu, Yun
Abstract: In this study, co-hydrothermal carbonization of rape straw and microalgae was conducted for clean hydrochar. The effect of different feedwater pH values (pH = 1, 3, 5, 7, 9, 12) on co-HTC and the mechanism of enhanced N, S, and O removal were revealed. The acidic and alkaline environment of the feedwater exacerbates the carbonization process. The higher heating value (HHV) of the hydrochar formed at pH = 1 reach 22.30 MJ/kg but the value of feedstock is only 13.87 MJ/kg. Deamination and deoxidation were the main method for protein degradation to remove N, S, and O from hydrochar. O/C, N/C, and S/C ratios of hydrochar reduced and the removal fraction of N, S, and O was 84.61%, 79.84%, and 81.80% of the hydrochar formed at pH = 1, respectively. Results showed that the acidic enhanced the content of aromatic clusters in aqueous increases, and the deoxidized hydrochar with high HHV was obtained. GC-MS analysis indicates that the aromatic clusters were formed in acidic and neutral conditions, while long-chain alkanes in alkaline. N-containing organic substances existing in the aqueous product were removed from the hydrochar by solid-liquid separation. Graphical abstract: Image 1 Highlights: HHV of the hydrochar is 22.30 MJ/kg at pH = 1 and for feedstock was 13.88 MJ/kg. Aromatic clusters were formed in acidic while long-chain alkanes in alkaline. Cleaning hydrochar from co-HTC of rape straw and microalgae was obtained. The mechanism of feedwater pH enhanced N, S, and O removal was revealed. The optimal removal rate of N, S, and O was 84.61%, 79.84%, and 81.80%.